2022
DOI: 10.3390/jof8080785
|View full text |Cite
|
Sign up to set email alerts
|

Actinomucor elegans and Podospora bulbillosa Positively Improves Endurance to Water Deficit and Salinity Stresses in Tomato Plants

Abstract: Fungal strains isolated from the rhizosphere of healthy Solanum lycopersicum were examined to mitigate symptoms of drought and salinity stresses. The fungal strains were identified as Actinomucor elegans and Podospora bulbillosa based on their DNA sequencing and morphological analysis. Additionally, the fungal strains were assayed for a number of plant growth promoting traits and abiotic stresses on solid media. Moreover, a greenhouse experiment was conducted and tomato seedlings were treated with 25% PEG or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 127 publications
2
4
0
Order By: Relevance
“…The reduction in the amount of chlorophyll could be the result of osmotic stress, which leads to substantial damage to chloroplast layers by increasing membrane permeability [61]. These findings resonate with established research, affirming that environmental stressors like salt stress and drought exert a proven propensity to deplete photosynthetic pigments in tomato leaves [62].…”
Section: Physiological Responses Of Tomato Plants To Water Quality An...supporting
confidence: 68%
“…The reduction in the amount of chlorophyll could be the result of osmotic stress, which leads to substantial damage to chloroplast layers by increasing membrane permeability [61]. These findings resonate with established research, affirming that environmental stressors like salt stress and drought exert a proven propensity to deplete photosynthetic pigments in tomato leaves [62].…”
Section: Physiological Responses Of Tomato Plants To Water Quality An...supporting
confidence: 68%
“…Osmotic stress causes a drop in Chl-I levels, which damages chloroplast layers by increasing the membrane permeability [48]. These results are in line with previous studies, which have demonstrated that environmental stressors, including dryness and salt stress, cause tomato leaves to lose their photosynthetic pigments [31,49].…”
Section: Discussionsupporting
confidence: 91%
“…The decreased chlorophyll could be due to damage to the thylakoid membranes, as a result of the destructive effect of reactive oxygen species (ROS) on chloroplasts [ 49 ]. Salinity and water deficits caused a significant increase in the formation of ROS [ 50 ]. Another explanation for the decrease in chlorophyll content could be that the osmotic stress seriously damages the chloroplast layers by increasing the penetrability of the membrane [ 51 ].…”
Section: Resultsmentioning
confidence: 99%